The Position of Married Daughters in Adoption in the Ngada Tribe Indigenous Community (Study of Supreme Court Decision Number 407 K/Pdt/2019) - Natigor Daulay, R. Fahmi; Muhammad, Ade Sultan (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This research examines the position of married daughters in child adoption practices within the Ngada ethnic community through an analysis of Supreme Court Decision Number 407 K/Pdt/2019. Using normative legal research methods and a case approach, the study reveals that although the Ngada community adheres to a patrilineal system that traditionally prioritizes sons in child adoption, there exists an adaptive mechanism in the form of the concept "women can hold the machete" that enables the adoption of married daughters for the purpose of performing traditional rituals. The Supreme Court in its decision acknowledged this flexibility of customary law by rejecting the argument that adoption applies only to male children, while affirming that the practice of adopting married daughters does not contradict Ngada customary law as long as it is done to continue and perform traditional rituals. This research demonstrates that customary law is not a static system but rather dynamic and continuously evolving according to community needs, and highlights the important role of courts in harmonizing traditional values with principles of justice and equality within the context of legal pluralism in Indonesia.